Clinical and Prognostic Features in a Young Adult Patient with de novo Myelodysplastic Syndrome presenting t(11;16) (q23; q24) - Viviane Lamim Lovatel; Luize Otero; Ercole Pietro Orlando; Claudia Diniz; Filipe Vicente dos Santos-Bueno; Bruno Almeida Lopes; Elaiza Almeida Antônio de Kós; Monica Kopischitz Praxedes Lusis; Eliana Abdelhay; Teresa de Souza Fernandez (Mediterranean Journal of Hematology and Infectious Diseases)
hematopoietic clonal neoplasms. MDS occurs mainly in elderly patients. KMT2A rearrangements (KMT2A-r) are rare in MDS, so little is known about their prognostic value. The present study describes the clinical characteristics of a young adult patient diagnosed with MDS-EB-2, presenting the t(11;16)(q23;q24). The Decitabine treatment was initiated since no matching donor was found. The patient showed improved anemia and thrombocytopenia. However, he still had severe neutropenia and clonal chromosomal alteration.   Two months after the fifth cycle of Decitabine, the patient presented a worsening of the clinical parameters with increased blast and evolution to AML. He was treated with intensification chemotherapy, but despite all efforts, the patient evolved to death. Treatment refractoriness and leukemia transformation suggest that t(11;16)(q23;q24) with KMT2A-r was associated with poor prognosis. This study reinforces the importance of characterizing new chromosomal alterations and their impact on prognosis in MDS.